Berry phase of the linearly polarized light wave along an optical fiber and its electromagnetic curves via quasi adapted frame - Körpınar, Talat; Demirkol, Rıdvan Cem (Taylor & Francis Ltd, 2020)
We review the geometric evolution of a linearly polarized light wave coupling into an optical fiber and the rotation of the polarization plane in a three dimensional ordinary space. We demonstrate that the evolution of a linearly polarized light wave is associated with the Berry phase or the geometric phase. We define other Fermi-Walker parallel transportation laws and connect them with the famous Rytov parallel transportation law for an electric field E, which is considered as the direction of the state of the linearly polarized light wave in the optical fiber in the 3D space. Later, we define a special class of magnetic curves called by quasi electromagnetic curves (qE M-curves), which are generated by the electric field E along the linearly polarized monochromatic light wave propagating in the optical fiber. In this way, not only we define a special class of linearly polarized point-particles corresponding to qE M-curves of the electromagnetic field along with the optical fiber in the 3D space, but we also calculate, both numerically and analytically, the electromagnetic force, Poynting vector, energy-exchanges rate, optical angular and linear momentum, and optical magnetic-torque experienced by the linearly polarizable point-particles along with the optical fiber in the 3D space.
Keywords: Polarized light wave; geometric phase; electromagnetic curves; electromagnetic force; optical angular momentum; magnetic force